Sustainable Management Of Rivers In Malaysia Involving All Stakeholders. - Chan, Ngai Weng (2004)
A11 over the world, including Malaysia, management of rivers is a central issue in this 21st Century. While government has always been traditionally entrusted with the responsibility of managing rivers, increasingly, the public, NGOs, industrialists, famers, and other stakeholders are playing a greater role.